Socioeconomic and geographical disparities in healthcare quality in Pakistan - Sohaib, Asharib; Hassan, Muhammad; Hussain, Muhammad; Hannan, Abdul (Journal of the Pakistan Medical Association, 2025)
Pakistan is a developing country with a population of 208 million. Approximately 63.6% of Pakistan’s population resides in rural areas, and 22% live below the poverty line.1 These factors, coupled with Pakistan allocating only 24,210 million Rs towards healthcare, which is less than 0.2% of the total budget, resulted in a significant portion of the lower-class population being deprived of adequate health services. The issue is further exacerbated by the uneven distribution of resources across different geographical regions by the government. Pakistan suffers greatly from socioeconomic discrepancy, with the top 1% of Pakistanis owning 30.2% of the country's total income, whereas the bottom 50% owning only 11.4%. To aggravate matters further, individuals must bear 76% of their medical expenditure; additionally, due to scattered hospital facilities, people in rural areas pay high travel costs. Furthermore, caste significantly influences healthcare quality. Certain healthcare programmes mainly focus on higher castes, neglecting lower castes, as program facilitators often belong to higher castes. This disparity is evident in maternal, newborn, and child health (MNCH) programmes as lower castes are largely excluded from participation both as facilitators and recipients.2 Additionally, access to Rural Health Centers is biased, the higher caste receives better treatment, whereas the lower caste is often ignored. Geographical health care disparities in Pakistan also present a significant barrier to universal access to quality health care.3 Pakistan has an in equate ratio of 16.59 CHI (Community Health Index), indicating that the most developed districts are 16.59 times healthier than the least developed districts. The disparity between rural (7.78) and urban (17.54) is about 10 points, highlighting substantial inequality.4 Furthermore, disparities exist between different provinces like Punjab, which has many healthy districts, in contrast to districts of Baluchistan Province, which are deprived of access to basic health care. Pakistan's rural population relies heavily on agriculture. To improve the health of individuals in this sector, comprehensive policy reforms should be implemented to address their medical needs. The Sehat Sahulat Programme is a commendable initiative where a family can access up to 400,000 PKR in primary healthcare and 60,000 PKR in secondary healthcare.5 This programme is currently available in KPK, Baluchistan, Kashmir, many regions of Punjab, and Tharparkar; however, it should be expanded to cover more areas of Sindh and Punjab to ensure broader access to healthcare services for rural populations.